(untitled) (Quarterly Journal of Econometrics Research, 2015)
This paper examines the relationship between intra-product trade and regional income distribution by empirical tests of co-integration and Granger causality with time series data from 1994 to 2013. The conclusion shows that intra-product trade and regional income distribution have a long-term equilibrium relationship. The exports of intra-product trade can significantly reduce the income gap between urban and rural residents, while the imports have a negative influence. At the meantime, the intra-product exports and imports are the one-way causal of income distribution. In addition, the capital contribution can enlarge the urban and rural income gap significantly. Education also has a negative influence, but it is non-significant.